Aspek Biopolitik Kebijakan Indonesia Dalam Menangani Pandemi Covid-19 - Mohamad Dziqie Aulia Al Farauqi; Dzulrifani Dzulrifani (Universitas 17 Agustus 1945 Jakarta, 2023)
Based on the World Health Organization report, Coronavirus disease 2019 (COVID-19) is a respiratory tract infection that has become an epidemic in approximately 213 countries around the world, including Indonesia. Before the first confirmed case of COVID-19 in Indonesia that the response given by the government was still not acting, it was seen how unaware the Indonesian government was in responding to the pandemic. Then, the situation in Indonesia is getting worse with a very significant increase in the number of cases occurring. Finally, the government also focused on handling this disease outbreak. In this case, the government provides recommendations and public policies for the community to prevent the spread of COVID-19. Through this study, the author aims to analyze the biopolitical aspects of handling COVID-19 by the Government of Indonesia. Therefore, the biopolitical aspect that focuses on Indonesia's policies in dealing with COVID-19 will be used as an analytical framework in this study. In addition, global health governance is also used as a reference to support the author's statement. To explain the actions of the Government of Indonesia, this study will use qualitative research with a focus on literacy observations related to this issue.